PENGARUH MEDIA PEMBELAJARAN INTERAKTIF PETA KEBUDAYAAN INDONESIA TERHADAP MINAT BELAJAR SISWA KELAS V SD INPRES TINGGIMAE - Salsabila; Putri Nailah Pratiwi; Herda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using interactive learning media on the learning interest of fifth-grade students at SD Inpres Tinggimae. This study employs a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The research subjects were all fifth-grade students in a single class, selected using total sampling. Data collection techniques included a learning interest questionnaire administered before (pretest) and after the intervention (posttest), supplemented by observation and documentation. The research instruments were first tested for validity and reliability, with results indicating the instruments were valid (r = 0.581; p = 0.004) and reliable (Cronbach’s Alpha = 0.860). Data analysis was conducted using the JASP software through normality tests and hypothesis testing. The results of the Shapiro–Wilk normality test indicated that the data were not normally distributed (p = 0.049), so the analysis proceeded using the Wilcoxon Signed-Rank Test. The results of the hypothesis test showed a significance level of p = 0.002 (p < 0.05), indicating a significant difference in students’ learning interest before and after the use of interactive learning media. Thus, it can be concluded that the use of interactive learning media has a significant effect on students’ interest in learning. Interactive learning media has been shown to create a more engaging and interactive learning environment that actively involves students. Therefore, it can serve as an innovative and effective alternative learning strategy to enhance students’ interest in learning in elementary school.